2013
DOI: 10.1007/s10753-013-9638-7
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Mediates MAPK–STAT3 Axis Activation in Bladder Epithelial Cells

Abstract: The role of Toll-like receptor 4 (TLR4) in immune cells is well characterized, but its biological properties in bladder epithelial cells (BECs), especially reciprocal crosstalk between mitogen-activated protein (MAP) kinase pathway and signal transducer and activator of transcription (STAT)3-mediated signal transduction elicited by TLR4 have not been demonstrated so far. The present studies were to demonstrate the signal transduction and inflammatory cytokine response elicited through activation of TLR4 in BEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…In addition, Chang et al (2012) revealed that the production of IL-10 in human monocyte-derived DCs from patients with gastric cancer is dependent on p38 mitogen-activated protein kinase (MAPK) signaling and on NF-κB activation. Consistent with previous reports, Ying et al (2013) demonstrated that the activation of MAPK, c-Jun, N-terminal kinase (JNK -Janus kinase), and signal transducer and activator of transcription 3 (STAT3) was associated with an increased IL-10 production in bladder epithelial cells. Finally, a recent study by Sanda et al (2013) revealed that T cell acute lymphoblastic leukemia cell lines and tissue samples showed the activation of a pathway involving TYK2, STAT1, and bcl-2, an antiapoptotic protein associated with numerous cancers (Barille-Nion et al, 2012).…”
Section: Il-10 Is Implicated In Tumorigenesis Through Multiplesupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, Chang et al (2012) revealed that the production of IL-10 in human monocyte-derived DCs from patients with gastric cancer is dependent on p38 mitogen-activated protein kinase (MAPK) signaling and on NF-κB activation. Consistent with previous reports, Ying et al (2013) demonstrated that the activation of MAPK, c-Jun, N-terminal kinase (JNK -Janus kinase), and signal transducer and activator of transcription 3 (STAT3) was associated with an increased IL-10 production in bladder epithelial cells. Finally, a recent study by Sanda et al (2013) revealed that T cell acute lymphoblastic leukemia cell lines and tissue samples showed the activation of a pathway involving TYK2, STAT1, and bcl-2, an antiapoptotic protein associated with numerous cancers (Barille-Nion et al, 2012).…”
Section: Il-10 Is Implicated In Tumorigenesis Through Multiplesupporting
confidence: 91%
“…The activation of IL-10 expression is known to be mediated by tolllike receptor (TLR)2, TLR3, and TLR4 in the presence of an infectious agent or pathogen-associated molecular patterns (PAMPs) (Bogunovic et al, 2011;Chang et al, 2012;Ying et al, 2013). It was found that IL-10 promotes tumor aggressiveness through the upregulation of CIP2A, an oncoprotein correlated with an accelerated cell growth and cancer progression .…”
Section: Il-10 Is Implicated In Tumorigenesis Through Multiplementioning
confidence: 99%
“…Further supporting the potential role of S100A8/A9 proteins in metatases, high expression of their receptor, RAGE, was present not only in metastatic Capan1, but also in the primary MiaPaCa2 cells, which cause a liver metastases rate overlapping that of Capan1 [47]. The other S100A8/A9 receptor, TLR4 [29], is reported to activate STAT3 [48]. The finding that this signal transducer was constitutively activated in all PDAC cell lines, supports the hypothesis that it plays role in this cancer type [49]; however the fact that it was not induced by the S100 studied molecules, suggests that they act mainly through RAGE engagement.…”
Section: Discussionmentioning
confidence: 94%
“…Because STAT3 can be activated by cytokines, including IL-6 in the tumor microenvironment, potential paracrine effects are likely to occur in vivo. Other factors are known to contribute to BCL-XL expression (41), and STAT3 can also be regulated by multiple signaling pathways, including G proteincoupled receptor and Toll-like receptor 4 (42,43). Of note, unphosphorylated STAT3 represents the bulk of total STAT3 and has been described to be oncogenic, in part, by modulating p-STAT3 gene targets with pro-oncogenic or pro-survival effects (c-Myc, c-fos, and BCL-XL as well as genes such as RANTES, cdc2, cyclin B1, IL-6, IL-8, Met, and M-RAS) through its cooperative binding with NF-B to specific B elements and/or other novel mechanisms (44).…”
Section: Discussionmentioning
confidence: 99%